2013
DOI: 10.1186/1475-2875-12-458
|View full text |Cite
|
Sign up to set email alerts
|

Malaria control in Botswana, 2008–2012: the path towards elimination

Abstract: BackgroundBotswana has made substantial progress towards malaria elimination across the country. This work assessed interventions and epidemiological characteristics of malaria in Botswana, during a period of decreasing transmission intensity.MethodsNational passive malaria surveillance data for five years (2008–2012) were analysed. A district-level, random effects model with Poisson regression was used to explore the association between malaria cases and coverage with long-lasting insecticide-treated nets (LL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 23 publications
2
31
1
Order By: Relevance
“…Only LLINs is found to be associated with a decline of malaria incidence in the present study, which is consistent with findings from Bangladesh [ 24 ] Rwanda [ 33 ], and Zambia [ 34 ]. In contrast to findings of this study, malaria incidence was associated with IRS coverage only in Botswana [ 22 ]. These findings imply that vector control interventions with a low coverage, or those that are focussed on selected VDCs only, cannot break down malaria transmission in VDCs or districts bordering malaria-endemic areas because the presence of vectors, a suitable climate and the continuous import of malaria cases facilitate the transmission cycle.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Only LLINs is found to be associated with a decline of malaria incidence in the present study, which is consistent with findings from Bangladesh [ 24 ] Rwanda [ 33 ], and Zambia [ 34 ]. In contrast to findings of this study, malaria incidence was associated with IRS coverage only in Botswana [ 22 ]. These findings imply that vector control interventions with a low coverage, or those that are focussed on selected VDCs only, cannot break down malaria transmission in VDCs or districts bordering malaria-endemic areas because the presence of vectors, a suitable climate and the continuous import of malaria cases facilitate the transmission cycle.…”
Section: Discussioncontrasting
confidence: 99%
“…Annual malaria incidence at the VDC level was analysed independently for spatial clustering (or hotspots) using the Getis-Ord Gi* statistic [ 21 23 ] in the Arc GIS software version 10 (ESRI, Redland, CA, USA). This statistic reflects whether differences between the local mean (i.e., the incidence for a VDC and its nearest neighbouring VDC within a district) was significantly different from the global mean (i.e., the overall incidence of all VDCs for that particular district) [ 22 , 24 , 25 ]. A statistically significant positive z-score value shows a hotspot for high incidence rates while a statistically significant negative z-score value for a VDC specifies local spatial clustering of low incidence rates [ 22 , 24 26 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interventions have continued in Botswana, from DDT spraying in the 1950s to the current program of bed net distribution, indoor residual spraying and winter biolarviciding, alongside passive surveillance (Chihanga et al 2013). Incidence forecasts can contribute to the surveillance program and guide the allocation of financial and material resources.…”
Section: Discussionmentioning
confidence: 99%
“…Countries engage in malaria control [33][34][35][36] and elimination [37] may learn from Bangladeshi experiences. Spatial analytical studies have shown a higher incidence of malaria in areas adjacent to these international borders [26].…”
Section: Spatially Explicit Mathematical Modelsmentioning
confidence: 99%